Analysis of School Innovation Program at SDN 23 Ampenan - Khairil Anwar; Auliya Khaerun Nisya; Al Fina Dwi Jayanti; Febrianti Zahrani; Rangga Adriansah; Siti Bulandari; Hatika Sari; Hilda Raodatul Jannah; M. Adi Ilham (Universitas Muhammadiyah Mataram, 2025)
Abstract: This article aims to analyze the implementation of school programs that occur at SDN 23 Ampenan. This research is important because school innovation programs are the main indicator of education quality. This type of research is descriptive qualitative, with data collection instruments in the form of observation sheets, open questionnaires, and field notes developed based on indicators of the implementation of the school's superior programs. The data collection method was carried out by means of a survey through the school environment introduction program (PLP-1). The data analysis technique used is qualitative analysis with the steps of data reduction, data presentation, and drawing conclusions. This article shows that the innovation program that was carried out can be implemented very well, the challenges faced during its implementation were the uncertain weather conditions that affected the school program implemented outside the classroom. The school programs of SDN 23 Ampenan have a positive impact on the quality of learning and character of students so that they can improve the quality of education at SDN 23 Ampenan.Abstrak: Artikel ini bertujuan untuk menganalisis pelaksanaan program-program persekolahan yang terjadi di SDN 23 Ampenan. Penelitian ini penting dilakukan karena program inovasi persekolahan menjadi indikator utama mutu pendidikan. Jenis penelitian ini adalah deskriptif kualitatif, dengan instrumen pengumpulan data berupa lembar observasi, angket terbuka, dan catatan lapangan yang dikembangkan berdasarkan indikator pelaksanaan program unggulan sekolah. Metode pengumpulan data dilakukan dengan cara survei melalui kegiatan program pengenalan lingkungan persekolahan (PLP-1). Teknik analisis data yang digunakan adalah analisis kualitatif dengan langkah-langkah reduksi data, penyajian data, dan penarikan kesimpulan. Artikel ini menunjukkan bahwa program inovasi yang dilakukan dapat diterapkan dengan sangat baik, tantangan yang dihadapi selama pelaksanaannya yaitu adanya kondisi cuaca yang tidak menentu yang mempengaruhi program sekolah yang dilaksanakan di luar kelas. Program-program sekolah SDN 23 Ampenan memberikan dampak positif terhadap kualitas pembelajaran dan karakter peserta didik sehingga dapat meningkatkan kualitas pendidikan di SDN 23 Ampenan.